An elusive case of acute abdomen in dengue fever - K. N., Ramesh; Gowda, Ambanna (International Journal of Research in Medical Sciences, 2017)
Currently dengue is endemic in all continents except Europe and epidemic dengue hemorrhagic fever occurs in Asia. Hemorrhagic manifestations observed at every stage of illness, they are probably the summation of ill understood virus as well as host factors that result in the incompetence of vescular endothelium.